Search for D+(s) → π+μ+μ− and D+(s) → π−μ+μ+ decays - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; Grünberg, Oliver; et al. (Physics letters, 2013)
A search for non-resonant D(s)+→π+μ+μ− and D(s)+→π−μ+μ+ decays is performed using proton-proton collision data, corresponding to an integrated luminosity of 1.0 fb−1, at s=7TeV recorded by the LHCb experiment in 2011. No signals are observed and the 90% (95%) confidence level (CL) limits on the branching fractions are found to be B(D+→π+μ+μ−)<7.3(8.3)×10−8, B(Ds+→π+μ+μ−)<4.1(4.8)×10−7, B(D+→π−μ+μ+)<2.2(2.5)×10−8, B(Ds+→π−μ+μ+)<1.2(1.4)×10−7. These limits are the most stringent to date.
Im Titel sind "+" und "-" hoch- und "(s)" tiefgestellt
LHCb Collaboration: R. Aaij, O. Aquines Gutierrez, S. Bachmann, A. Bien, J. Blouw, M. Britsch, A. Di Canto, F. Dordei, C. Färber, M. Fontana, E. Gersabeck, O. Grünberg, S. Hansmann-Menzemer, T. Hartmann, A. Jaeger, K. Kreplin, G. Krocker, B. Leverington, C. Linn, J. Marks, M. Meissner, T. Nikodem, D. Popov, M. Schmelling, P. Seyfert, S. Stahl, J. van Tilburg, U. Uwer, D. Volyanskyy, C. Voß, H. Voss, R. Waldi, S. Wandernoth, D. Wiedner, M. Zavertyaev, A. Zhelezov und weitere 587
Gesehen am 27.04.2021